ETNOMÍDIA E INTERSECCIONALIDADES: práticas comunicativas das mulheres Guarani e Kaiowá no Instagram - MYLENA GARCETE ROCHA (2024)
The research analyzed the communicative practices of women from Kuñangue Aty Guasu, the Assembly of Kaiowá and Guarani Women, in the southern region of Mato Grosso do Sul. Additionally, it investigated the relationship of these women with communication as a way of assuming the leading role in their narratives, in contrast to the silencing imposed by the hegemonic media (Monteiro, 2017; Urquiza, 2017; Silva, 2018). In a context marked by violence, gender inequality and several other markers of oppression, the research explored the relationship between Guarani and Kaiowá women with intersectionality and the use of social media tools, specifically Instagram, as an ethnomedia (Tupinambá, 2016; Santi; Araújo, 2019, 2021, 2022; Freitas, 2021; Nascimento, 2020). Based on Fernanda Carrera's (2021a, 2021b) intersectional roulette proposal, it analyzed posts published from January to June 2023 to understand the impacts of oppression on the practice of communication of indigenous women in the Assembly and to understand how they want to be represented and how to negotiate their identities. With intersectional roulette and the contribution of Discourse Analysis (Maingueneau, 2008; Amossy, 2008), it is possible to understand how they have used the tools of the Assembly Instagram to break, confirm or even reinvent the image built for centuries about what it means to be an indigenous woman.